A Comparison of In-flight and Ground-Based Emergency Medical Events on the Clinical Demand for Outreach Medical Services at Taoyuan International Airport, Taiwan - Lo, Chin-Hsiang; Shiao, Yu-Feng; Hsu, Shih-Tien (Frontiers in Public Health, 2021)
Background: Limited information is available covering all medical events managed by the airport-based outreach medical service. This study explores the clinical demand for emergency medical outreach services at Taoyuan International Airport (TIA), Taiwan. Methods: Electronic medical records collected from TIA medical outreach services from 2017 to 2018, included passengers’ profiles, flight information, events location, chief complaints, diagnosis (using ICD-9 -CM codes), and management outcomes. Medical events distribution was stratified by location and ages, and were compared statistically. Results: Among 1,501 eligible records, there were 81.7% ground-based emergency medical events (GBME), 15.0% in-flight medical events (IFME) managed after scheduled landing, and 1.3% IFME leading to unscheduled diversion or re-entry to TIA. The top three GBME diagnoses were associated with neurological (23.3%), gastrointestinal (21.2%), and trauma-related (19.3%) conditions. The top three IFME diagnosis that prompted unscheduled landings via flight diversion or re-entry were neurological (47.4%), psychological (15.8%), and cardiovascular (10.5%). The chief complaints that prompted unscheduled landings were mostly related to neurological (42.1%), cardiovascular (26.3%), and out-of-hospital cardiac arrest (OHCA) (10.5%) symptoms. A higher frequency of IFME events due to dermatologic causes in patients aged ≤ 18 years compared with adults and older adults (19% vs 1.5% and 0, respectively); and a higher frequency of IFME due to cardiovascular causes in adults ≥ 65 years compared with patients aged ≤ 65 (15.1% vs 9%). Among all IFME patients, six out-of-hospital deaths occurred among passengers from scheduled landings and two deaths occurred among 18 IFME passengers who were transferred to local hospitals from flight diversion or re-entry. A statistically significant difference in outcomes and short-term follow-up status was found between patients with IFME and those with GBME (p < 0.001). Conclusion: Ground-based emergency medical events exceeded in-flight medical events at TIA. The most frequent events were related to neurological, gastrointestinal symptoms or trauma. Results of this study may provide useful information for training medical outreach staff and preparing medical supplies to meet the clinical demand for airport medical outreach services.